Neighborhood poverty and hemodynamic, neuroendocrine, and immune response to acute stress among patients with coronary artery disease. (February 2019) - Sullivan, Samaah; Kelli, Heval M.; Hammadah, Muhammad; Topel, Matthew; Wilmot, Kobina; Ramadan, Ronnie; Pearce, Brad D.; Shah, Amit; Lima, Bruno B.; Kim, Jeong Hwan; Hardy, Shakia; Levantsevych, Oleksiy; et al.
Highlights: Patients in high poverty neighborhoods had a blunted sympathetic stress response. Results were specific to reactivity to mental stress challenge. A blunted hemodynamic stress response was not observed during exercise stress. Neighborhood poverty may lead to poor health through a blunted stress response. Abstract: Living in neighborhoods characterized by poverty may act as a chronic stressor that results in physiological dysregulation of the sympathetic nervous system. No previous study has assessed neighborhood poverty with hemodynamic, neuroendocrine, and immune reactivity to stress. We used data from 632 patients with coronary artery disease. Patients' residential addresses were geocoded and merged with poverty data from the 2010 American Community Survey at the census-tract level. A z-transformation was calculated to classify census tracts (neighborhoods) as either having 'high' or 'low' poverty. Systolic blood pressure, diastolic blood pressure, heart rate, rate-pressure product, epinephrine, interleukin-6, and high-sensitivity C-reactive protein were measured before and after a public speaking stress task. Multilevel models were used for repeated measures and accounting for individuals nested within census tracts. Adjusted models included demographics, lifestyle and medical risk factors, and medication use. Another set of models included propensity scores weighted by the inverse probability of neighborhood status for sex, age, race, and individual-level income. The mean age was 63 years and 173 were women. After adjusting for potential confounders, participants living in high (vs. low) poverty neighborhoods had similar hemodynamic values at rest and lower values during mental stress for systolic blood pressure (157 mmHg vs. 161 mmHg; p = 0.07), heart rate (75 beats/min vs. 78 beats/min; p = 0.02) and rate-pressure product (11839 mmHg x beat/min vs 12579 mmHg x beat/min; p = 0.01). P-values for neighborhood poverty-by-time interactions were <0.05. Results were similar in the propensity weighted models. There were no significant differences in inflammatory and epinephrine responses to mental stress based on neighborhood poverty status. A blunted hemodynamic response to mental stress was observed among participants living in high poverty neighborhoods. Future studies should explore whether neighborhood poverty and blunted hemodynamic response to stress translate into differences in long-term cardiovascular outcomes.